2008
DOI: 10.1177/0884533608323421
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Nutrition Status in Crohn's Disease Patients Receiving Infliximab Therapy

Abstract: Aim There is limited information on the nutrition impact of antitumor necrosis factor-α treatment in adult Crohn's disease (CD). This study was performed to examine the effect of a 6-month course of infliximab on enterocyte function, nutrient status, metabolism, and body composition in these patients. Methods Seven CD patients were assessed for disease activity, enterocyte function, and body composition prior to, after 6 weeks, and after 6 months of infliximab treatment. Measurements included (1) disease act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…It should be noted that all patients had the body water percentage within normal values, so that FM and LM could not be affected by disturbances in the patients' hydration status. 21 Increased FM after treatment with anti-TNF in patients with CD has also been reported in the study by Wiese et al 34 The gain of FM in patients who achieved clinical remission after biological therapy can be explained by factors such as improvement in the quantity and quality of food intake due to absence of symptoms, less catabolism secondary to reduction of inflammation and, last, TNF-α blockade. TNF is a mediator of cachexia induced by inflammation.…”
Section: Discussionsupporting
confidence: 52%
“…It should be noted that all patients had the body water percentage within normal values, so that FM and LM could not be affected by disturbances in the patients' hydration status. 21 Increased FM after treatment with anti-TNF in patients with CD has also been reported in the study by Wiese et al 34 The gain of FM in patients who achieved clinical remission after biological therapy can be explained by factors such as improvement in the quantity and quality of food intake due to absence of symptoms, less catabolism secondary to reduction of inflammation and, last, TNF-α blockade. TNF is a mediator of cachexia induced by inflammation.…”
Section: Discussionsupporting
confidence: 52%
“…Findings concerning the effects of anti-TNF-α therapy on energy metabolism in CD patients are controversial. Wiese et al (22) reported that RQ tended to increase after infliximab therapy ( p  = 0.07), whereas no increase was detected in the REE value. In contrast, Steiner et al (23) working with pediatric patients reported a significant reduction in RQ during parenteral nutrition after infliximab therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported improvements in nutritional status and metabolism after infliximab therapy but did not measure vitamin D levels per se. 29,30 …”
Section: Discussionmentioning
confidence: 99%